DISSERTATION TITLE: EXTRACTION OF CONTINUOUS CELLULOSE FIBER FROM MENGKUANG LEAVES: THE INFLUENCE OF EXTRACTION PROCESS PARAMETERS - HAMIZOL, MUHAMMAD SYAHMI (2015)
The focus of this study was to obtain continuous cellulose fiber (CCF) extracted from mengkuang leaves. Chemical means was used for the extraction process. Treatments employed were alkali and combined alkali - bleach treatment. Each treatment was varied s in terms of the chemical concentration and soaking time. The objective of the work was to investigate the influence of these extraction parameters on cellulose content, morphology and tensile strength of the extracted CCF. Selected CCF were further employed in composite fabrication and characterized for their tensile strength,